Impact of a community-based naloxone distribution program on opioid overdose death rates - Naumann, Rebecca B. (Drug Alcohol Depend, 2019)
BACKGROUND: In August 2013, a naloxone distribution program was implemented in North Carolina (NC). This study evaluated that program by quantifying the association between the program and county-level opioid overdose death (OOD) rates and conducting a cost-benefit analysis. METHODS: One-group pre-post design. Data included annual county-level counts of naloxone kits distributed from 2013-2016 and mortality data from 2000-2016. We used generalized estimating equations to estimate the association between cumulative rates of naloxone kits distributed and annual OOD rates. Costs included naloxone kit purchases and distribution costs; benefits were quantified as OODs avoided and monetized using a conservative value of a life. RESULTS: The rate of OOD in counties with 1-100 cumulative naloxone kits distributed per 100,000 population was 0.90 times (95% CI: 0.78, 1.04) that of counties that had not received kits. In counties that received >100 cumulative kits per 100,000 population, the OOD rate was 0.88 times (95% CI: 0.76, 1.02) that of counties that had not received kits. By December 2016, an estimated 352 NC deaths were avoided by naloxone distribution (95% CI: 189, 580). On average, for every dollar spent on the program, there was $2,742 of benefit due to OODs avoided (95% CI: $1,237, $4,882). CONCLUSIONS: Our estimates suggest that community-based naloxone distribution is associated with lower OOD rates. The program generated substantial societal benefits due to averted OODs. States and communities should continue to support efforts to increase naloxone access, which may include reducing legal, financial, and normative barriers.